BS EN 2714-014. Aerospace series. Cables, electrical, single and multicore for general purpose. Operating temperatures between - 55 °C and 260 °C. Part 014. DR family, 4 to 11 cores, taped, screened (braided) and jacketed, UV laser printable. Product standard (6th July 2023) - British Standards Institution,
No abstract available